Two findings of portal hypertension: Evaluation of correlation between serum-ascites albumin gradient and esophageal varices in non-alcoholic cirrhosis - Ulvi DEMİREL; Melih KARINCAOĞLU; Murat MM HARPUTLUOĞLU; Mehmet ATEŞ; Yüksel SEÇKİN; Bülent YILDIRIM; Fatih HİLMİOĞLU (Turkish Journal of Gastroenterology, 2019)
-